2012
DOI: 10.1097/prs.0b013e3182454352
|View full text |Cite
|
Sign up to set email alerts
|

Amifostine Remediates the Degenerative Effects of Radiation on the Mineralization Capacity of the Murine Mandible

Abstract: Background Although radiotherapy is a cornerstone in head and neck cancer treatment it causes substantial morbidity to the normal adjoining bone. Our specific aim is to assess the radioprotective effect of Amifostine (AMF) therapy on the mineralization of the mandible using micro-computed tomography (μCT). We hypothesize that AMF will safeguard the mandible from radiation-induced disruption of the mineralization process and the associated failure of new bone creation. Methods Male Sprague Dawley rats were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Increased vessel separation translates into a decrease in vascular density. [20] Taken together, these two stereologic metrics may suggest inadequate blood supply to surrounding tissues. Insufficient blood supply hampers the growth of viable bony regenerate in the distraction gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased vessel separation translates into a decrease in vascular density. [20] Taken together, these two stereologic metrics may suggest inadequate blood supply to surrounding tissues. Insufficient blood supply hampers the growth of viable bony regenerate in the distraction gap.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that radiotherapy can play a significant role in impairing the healing mechanisms in regenerate bone. [18, 12, 19, 20] Therefore, the purpose of this study was to specifically develop a novel isogenic rat model of impaired vasculogenesis of the regenerate mandible in order to determine quantifiable metrics of vascular injury and associated damage. Once the specific level and extent of injury is ascertained, cell based therapies can be utilized to remediate and assuage the damage, restore the ability to heal bone, and permit the utilization of Distraction Osteogenesis in this challenging patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Rats receiving Amifostine were administered a 100mg/kg dorsal subcutaneous injection 45 minutes prior to radiation, a dose previously derived and utilized by our laboratory in published studies. 11,12 Just prior to radiation administration, animals underwent closed chamber induction with inhalational isoflurane. The animal was then placed in the radiation chamber and covered with a protective lead shield that exposed only a 4cm diameter circular region directly overlying the expander.…”
Section: Methodsmentioning
confidence: 99%
“…Specimens receiving amifostine were administered a 100-mg/kg dorsal subcutaneous injection 45 minutes before irradiation, a dose previously developed by our laboratory and used in published studies. 11,12 Animals underwent closed-chamber induction with inhalational isoflurane before being placed in the radiation chamber and covered with a protective lead shield that exposed only the left hemimandible. Low-flow isoflurane and oxygen were administered continuously duration irradiation, which lasted approximately 5 minutes for each fractionated dose.…”
Section: Methodsmentioning
confidence: 99%
“…810 In our laboratory, we have demonstrated that the cytoprotective properties exhibited by amifostine in soft tissues are also translatable to bone, as prophylactic amifostine administration was shown to preserve new bone formation in irradiated murine mandibles after distraction osteogenesis and fracture repair. 11,12 …”
mentioning
confidence: 99%